MSC response to pH levels found in degenerating intervertebral discs - Wuertz, Karin (2009)
Painful degenerative disc disease is a major health problem and for successful tissue regeneration, MSCs must endure and thrive in a harsh disc microenvironment that includes matrix acidity as a critical factor. MSCs were isolated from bone marrow of Sprague-Dawley rats from two different age groups (<1 month, n=6 and 4–5 months, n=6) and cultured under four different pH conditions representative of the healthy, mildly or severely degenerated intervertebral disc (pH 7.4, pH 7.1, pH 6.8, pH 6.5) for 5 days. Acidity caused an inhibition of aggrecan, collagen-1 and TIMP-3 expression, as well as a decrease in proliferation and viability and was associated with a change in cell morphology. Ageing had generally minor effects but young MSCs maintained greater mRNA expression levels. As acidic pH levels are typical of increasingly degenerated discs, our findings demonstrate the importance of early interventions and predifferentiation when planning to use MSCs for reparative treatments.